Self-perception of voice and knowledge of vocal health and hygiene in Candomblé religious leaders in Brazil - Faustino, Kenya Ayo-Kianga da Silva; Moreti, Felipe [UNESP]; Behlau, Mara (Soc Brasileira Fonoaudiologia, 2024)
Purpose: To verify possible complaints, voice and aerodigestive symptoms, singing voice handicap, and knowledge of vocal health and hygiene in Candombl & eacute; religious leaders in Brazil. Methods: The study comprised 112 individuals who filled out a questionnaire with their identification and characterization, the stratified classification of their professional activities, and their self-perception of voice. Three self-assessment protocols- VoiSS, QSHV, and MSHI- were also used. Results: The self-assessment of voice ranged from average to good. VoiSS mean total score was 23.04, which is above the cutoff. QSHV mean score was 23.54 points, which is near the cutoff. MSHI mean score (the perception of singing voice handicap) was 25.66 points. There was a substantially strong positive correlation between VoiSS and MSHI total scores (0.789; p<0.001). Women had higher limitation scores (p=0.012) and total scores (p=0.012) in VoiSS and higher handicap scores (p=0.038) in MSHI. Level I professionals- vocal elite (singers and actors)- had significantly higher QSHV scores than those in levels IV (p=0.010) and V (p=0.008). Most respondents had not visited an otorhinolaryngologist (89.29%) within the last year and had not been submitted to speech therapy (83.04%) for voice complaints. Conclusion: Candombl & eacute; leaders, particularly women, perceived voice symptoms and singing voice handicaps, with no relationship with their knowledge of vocal health and hygiene. Despite the complaints, most subjects reported not having visited health professionals responsible for voice care within the last year.
Keywords: Voice; Religious Personnel; Singing; Self-Testing; Surveys and Questionnaires; Knowledge; Signs and Symptoms; Speech; Language and Hearing Sciences